The Comparison of Indonesian and American Consumer Protection Laws: What and How? - Wibowo, Dwi Edi (Faculty of Law, Universitas Pattimura, 2024)
Introduction: In this rapidly developing era of globalization, consumer protection has become an important global issue, with consumers having the right to receive adequate protection from the government and relevant legal institutions in various aspects such as product safety, service quality, and fair transactions.Purposes of the Research: This research aims to analyze the comparison of consumer protection legal substances between Indonesia and the United States, as well as to identify the differences and similarities in the implementation of consumer protection laws in both countries.Methods of the Research: This research employs normative legal research methods with a conceptual approach, analyzing primary, secondary, and tertiary legal materials through literature review, and applies descriptive-qualitative analysis to compare the substance and implementation of consumer protection laws in Indonesia and the United States.Results of the Research: Research findings show that consumer protection laws in Indonesia and the United States have significant differences that reflect each country's legal system. Indonesia relies on the Consumer Protection Act with a focus on basic consumer rights and non-litigation dispute resolution, while the US combines common law with federal and state laws, providing broader protection including data privacy and product safety. The implementation of laws in both countries also differs, with Indonesia prioritizing non-litigation mediation through BPSK (Consumer Dispute Settlement Body), while the US has a strong litigation system including class action mechanisms. Nevertheless, both countries face similar challenges in the digital era and equally emphasize the role of supervisory institutions to ensure effective law implementation.